An aryl isonitrile compound with an improved physicochemical profile that is effective in two mouse models of multidrug-resistant Staphylococcus aureus infection. (December 2019) - Mohammad, Haroon; Kyei-Baffour, Kwaku; Abutaleb, Nader S.; Dai, Mingji; Seleem, Mohamed N.
Highlights: Compound 35, a synthetic aryl isonitrile compound, was investigated against MRSA. MRSA resistance to compound 35 was not observed after 10 serial passages. Compound 35 rapidly permeates across intestinal epithelial (Caco-2) cells. The half-life of compound 35 is >11 h when incubated with human liver microsomes. Compound 35 noticeably reduces the MRSA burden in murine skin and thigh infection models. Abstract: Objectives: The aim of this study was to investigate the antibacterial activity of a synthetic aryl isonitrile compound (35 ) that was developed as part of a compound library to identify new antibacterial agents effective against methicillin-resistant Staphylococcus aureus (MRSA). Methods: Compound 35 was evaluated against MRSA isolates by the broth microdilution assay and for toxicity to mammalian keratinocytes using the MTS assay. A multistep resistance selection assay was conducted to investigate MRSA resistance development to 35 . A Caco-2 bidirectional permeability assay was employed to evaluate the ability of 35 to permeate across the gastrointestinal tract, and compound 35 was incubated with human liver microsomes to determine susceptibility to hepatic metabolism. Finally, compound 35 was evaluated in an uncomplicated MRSA skin infection mouse model and an MRSA neutropenic thigh infection mouse model. Results: Compound 35 inhibited the growth of MRSA clinical isolates at 2–4 μM and was non-toxic to human keratinocytes. No resistance formation was observed with MRSA against compound 35 after 10 serial passages. In a murine skin wound model, compound 35 significantly reduced the burden of MRSA, similar to the antibiotic fusidic acid. Compound 35 exhibited a marked improvement both in permeability and stability to hepatic metabolism (half-life >11 h) relative to the first-generation lead compound. In a neutropenic thigh infection mouse model, compound 35 successfully reduced the burden of MRSA in immunocompromised mice. Conclusion: In summary, compound 35 was identified as a new lead aryl isonitrile compound that warrants further investigation as a novel antibacterial agent.